Neuthropil-to-Lymphocyte Ratio Correlation with Pneumonia Severity Index in COVID-19 Patients - Hendrastutik Apriningsih; Nurhasan Agung Prabowo; Reviono; Betty Suryawati; Tonang Dwi Ardyanto (Nusantara Science and Technology Proceedings, 2023)
COVID-19 is still a major problem and characterized by the development and progression of inflammatory responses. Assessment of disease degree includes several tools, such as the pneumonia severity index (PSI). However, because the pandemic occurs in all regions in Indonesia, not all health facilities have a complete diagnostic tool to assess the severity of pneumonia. It is necessary to have an easy, inexpensive, and readily available examination to determine the COVID-19 disease's severity, such as Neutrophil-to-Lymphocyte Ratio (NLR). The purpose of this study was to determine the correlation between NLR and PSI in COVID-19 patients. The research was carried out on the COVID-19 ward of Universitas Sebelas Maret (UNS) Hospital in February 2021. Examination of laboratory parameters and X-rays was carried out when the patients entered the Emergency Room at the hospital. A prospective cohort study, with the population being patients >18 years old with mild to critical COVID-19 and being admitted from February to March 2021. Statistical analysis was conducted using the Pearson correlation test with SPSS 25, in which case p was deemed significant if it was <0.05. Results were obtained from 49 COVID-19 patients treated in the COVID-19 ward, whose mean age was 49.83 + 13.31, NLR and PSI were 8.85 + 13.25, 61.673 + 26.635, respectively. There was a strong positive correlation between NLR and PSI (p = 0.001; r = 0.488). NLR was correlated with PSI in COVID-19 patients.